Hubungan Pendidikan Ibu dan Pendapatan Keluarga dengan Praktik Perawatan Nifas di Wilayah Kerja Puskesmas Purwodadi II Kabupaten Grobogan - Umi Kasanah; Siti Fatimah Pradigdo; R. Djoko Nugroho (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
The good postpartum care is an effort to prevent maternal mortality ratio (MMR). MMR in Grobogan Regency in 2018 was 152,5 per 100.000 live birth, higher than MMR in Central Java Province, which was 78,6 per 100.000 live birth. The purpose of this study is to analyze the relationship between maternal education and family income with postpartum care practices. This was explanatory research type and cross sectional study design. The population in this study were mothers giving birth in January - June 2019 in number 140 and sample choosen by simple random sampling with a minimum sample size of 54 people. Data analysis is concluding univariat and bivariate (descriptive and analytic) by using chi – square with continuity correction method with α 5%. The results of this study are the majority of respondents are post-partum mothers with basic education (61.1%), high family income (55.6%) and good postpartum care practices (64.8%). The percentage of good postpartum care practices was greater for mothers who attended further education (76.2%) and low family income (70.8%). The results of data analysis showed that there was no relationship between maternal education (pvalue = 0.270) and family income (pvalue = 0.588). Recommendation to provide counseling and interpersonal communication to postpartum mothers so that the practice is even better.